Relationship of Weight Length and Condition Factors of Sengarat Fish (Belodontichthys dinema, Bleeker 1851) from Kampar River, Riau Province - Indra Lesmana; Benny Heltonika; Novreta Ersyi Darfia; Isma Mulyani; Garindi Endrina Putra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Sengarat fish (Belodontichthys dinema, Bleeker 1851) is one of the most important freshwater fish. No research has been Relationship of weight length and condition Factors of Sengarat Fish in Kampar River waters. Sampling was conducted in March-October 2022 using gill net fishing gear and bubu in the Kampar watershed in the Buluh Nipis Village area, Siak Hulu District, Kampar Regency, Riau. Data analyzed using Ms Excel 2010 application from the results of fish growth pattern analysis (n = 16) showed a value = 0.0118 and b value = 2.7765, R2 of 0.976. The growth pattern of sengarat fish is negative allometric. The condition factor of sengarat fish is relatively good, with a value of 0.497 and Wr = 129.79.